Coupling of PAK-Interacting Exchange Factor PIX to GIT1 Promotes Focal Complex Disassembly - Zhao, Zhou-shen (American Society for Microbiology, 2000)
The p21-activated kinase PAK is targeted to focal complexes (FCs) through interactions with the SH3 domains of the PAK-interacting exchange factor PIX and Nck. PIX is a Rac GTP exchange factor that also binds the G-protein-coupled receptor kinase-interacting protein known as GIT1. Overexpression of GIT1 in fibroblasts or epithelial cells causes a loss of paxillin from FCs and stimulates cell motility. This is due to the direct interaction of a C-terminal 125-residue domain of GIT1 with paxillin, under the regulation of PIX. In its activated state, GIT1 can promote FC disassembly independent of actin-myosin contractile events. Additionally, GIT directly couples to a key component of FCs, focal adhesion kinase (FAK), via a conserved Spa2 homology domain. We propose that GIT1 and FAK cooperate to promote motility both by directly regulating focal complex dynamics and by the activation of Rac.